SOME RESULTS ON DELTA-PRIMARY SUBMODULES OF MODULES - (:unkn) unknown (YILDIZ TECHNICAL UNIV, 2018)
In this paper we investigate delta- primary submodules which unify prime submodules and primary submodules. Our motivation is to extend the concept of delta- primary ideals into delta- primary submodules of modules over commutative rings. A number of main results about prime and primary submodules are extended into this general framework.
Keywords: Expansion of submodules; delta-primary submodules; multiplication modules